IGF-I Influences Everolimus Activity in Medullary Thyroid Carcinoma - Gentilin, Erica; Di Pasquale, Carmelina; Rossi, Martina; Tagliati, Federico; Gagliano, Teresa; Rossi, Roberta; Pelizzo, Mariarosa; Merante Boschin, Isabella; degli Uberti, Ettore C.; Zatelli, Maria Chiara (Frontiers in Endocrinology, 2015)
Context Medullary thyroid carcinoma (MTC) is a rare tumor originating from thyroid parafollicular C cells. It has been previously demonstrated that insulin-like growth factor I (IGF-I) protects MTC from the effects of antiproliferative drugs. Everolimus, an mTOR inhibitor, has shown potent antiproliferative effects in a human MTC cell line, TT, and in two human MTC primary cultures. Objective To verify whether IGF-I may influence the effects of everolimus in a group of human MTC primary cultures. Design We collected 18 MTCs that were dispersed in primary cultures, treated without or with 10 nM–1 μM everolimus and/or 50 nM IGF-I. Cell viability was evaluated after 48 h, and calcitonin (CT) secretion was assessed after a 6 h incubation. IGF-I receptor downstream signaling protein expression profile was also investigated. Results Everolimus significantly reduced cell viability in eight MTC [by 20%; P < 0.01 vs. control; everolimus-responders (E-R) MTCs], while cell viability did not change in 10 MTCs [everolimus-non-responders (E-NR) MTCs]. In E-R MTCs, IGF-I blocked the antiproliferative effects of everolimus that did not affect CT secretion, but blocked the stimulatory effects of IGF-I on this parameter. IGF-I receptor downstream signaling proteins were expressed at higher levels in E-NR MTC as compared to E-R MTCs. Conclusion IGF-I protects a subset of MTC primary cultures from the antiproliferative effects of everolimus and stimulates CT secretion by an mTOR mediated pathway that, in turn, may represent a therapeutic target in the treatment of aggressive MTCs.